Agile marketing sprint model: A rapid-response approach in handling viral social media backlash - Yusoff, Yuslina; Mustapha, Ramlan; Yusuf, Norazmila; Sapia, Nur Shaliza; Mohd Zain, Rogayah (Journal of Islamic, Social, Economics and Development, 2026)
Standard crisis communication models for a drained media environment are becoming increasingly irrelevant in the face of viral social media outbreaks Today’s institutional crises claim that responses not only strategically appropriate but also must be fast, nimble and synchronized. This study introduces the Agile Crisis Sprint Model (ACSM) as part of a broader agile marketing ecosystem to enhance and build up a quick response while still aligning strategy, brand consistency, and compliance characteristics. This is an exploration and applicability of 10 components for agile marketing and crisis response, where Nominal Group Technic (NGT) method was employed to solicit feedback from seven experts. Result Based on the result it seems that ACPM, Hybrid Sprint Synchronization Tool and RIAF were scored as (12) a most importance level point which indicate that all the listed element proposed score are highly approved (consensus above 75%). ACSM also scored as applicable, indicating its importance as a rapid-response tool for management of viral crises through microsprints, cross functional coordination and real-time monitoring of social media. The practical implication is that the study presents a structured, evidence-based model for institutions to teach skillful crisis response behaviors, faster decision-making and increased professional resistance in high-stress digital environments. Its contribution is theoretical, as its suggested extension of agile to crisis communication particularly in marketing area.